Emotional Dynamics and Communication: Their Influence on Husbands' Sexual Satisfaction with Working Wives - Monica Ayu Yuliasari; Trubus Raharjo (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The increasing number of working wives created new dynamics in marital life, particularly in emotional aspects and communication, which could affect husbands' sexual satisfaction. The dual role of wives as workers and partners in the household posed challenges in maintaining a balance between work demands and personal relationships. This study aimed to analyze the influence of emotion regulation and interpersonal communication on the sexual satisfaction of husbands with working wives. The research employed a quantitative approach with a correlational design. Participants consisted of husbands with working wives, selected using purposive sampling. Data were collected using emotion regulation scales, interpersonal communication scales, and sexual satisfaction scales. Data analysis was conducted using multiple linear regression techniques to examine the relationships between variables. The results indicated that emotion regulation and interpersonal communication had a significant relationship with husbands' sexual satisfaction. Interpersonal communication had a greater influence than emotion regulation in explaining variations in sexual satisfaction. These findings provided implications for psychological interventions and marital counseling by emphasizing the importance of communication skills in enhancing relationship quality. Training in interpersonal communication and emotional management could be an effective strategy in maintaining marital satisfaction, particularly for couples where the wife was employed. Peningkatan jumlah istri yang bekerja menciptakan dinamika baru dalam kehidupan pernikahan terutama dalam aspek emosional dan komunikasi yang dapat memengaruhi kepuasan seksual suami. Peran ganda istri sebagai pekerja dan pasangan dalam rumah tangga menimbulkan tantangan dalam menjaga keseimbangan antara tuntutan pekerjaan dan hubungan pribadi. Penelitian ini bertujuan untuk menganalisis pengaruh regulasi emosi dan komunikasi interpersonal terhadap kepuasan seksual suami yang memiliki istri bekerja. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Partisipan terdiri dari suami yang memiliki istri bekerja dengan teknik pengambilan sampel purposive sampling. Data dikumpulkan menggunakan skala regulasi emosi skala komunikasi interpersonal dan skala kepuasan seksual. Analisis data dilakukan menggunakan teknik regresi linear berganda untuk melihat hubungan antara variabel. Hasil penelitian menunjukkan bahwa regulasi emosi dan komunikasi interpersonal memiliki hubungan yang signifikan dengan kepuasan seksual suami. Komunikasi interpersonal memiliki pengaruh lebih besar dibandingkan regulasi emosi dalam menjelaskan variasi kepuasan seksual. Temuan ini memberikan implikasi bagi intervensi psikologis dan konseling pernikahan dengan menekankan pentingnya keterampilan komunikasi dalam meningkatkan kualitas hubungan pasangan. Pelatihan komunikasi interpersonal dan pengelolaan emosi dapat menjadi strategi efektif dalam menjaga kepuasan dalam pernikahan terutama bagi pasangan dengan istri bekerja.